Numerical investigation of the flow over delta wing and reverse delta wing - Ludin@Jamaluddin, Hani; Omar, Ashraf Ali; Asrar, Waqar (Springer International publishing, 2015)
Abstract This study aims to give some thoughts and initial understanding of passive wake vortex alleviation by introducing add-ons devices onto the aircraft, which are delta wing (DW) and reverse delta wing (RDW). However, as a preliminary investigation, the study has treated these devices separately from the aircraft in order to clearly visualize the wake vortex formation behind the wing as a standalone. Simulations were performed using RANS turbulence model. The results were obtained and quantified at measurement section locations downstream, of x/c=1.359 and x/c=3.418 measured from leading edge point of the model. Comparison between numerical and experimental results has shown good agreement in term of aerodynamic forces for RDW, whereas the comparison is not so good for DW as far as the prediction of drag coefficient is concerned. Although the simulations capture vortex roll-up trends, the size of the vortex is not predicted correctly by RANS turbulence model. Overall, it can be concluded from the results that the wake vortex generated from DW exhibit higher tangential velocity magnitude and circulation than the one generated from RDW at a particular angle of attack (AOA) between 20º to 30º.